2012
DOI: 10.5694/mja12.10313
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised controlled trial of vascular risk factor management in general practice

Abstract: Australian New Zealand Clinical Trials Registry ACTRN12607000423415.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 18 publications
0
59
1
Order By: Relevance
“…Similarly, in a cluster randomized controlled trial, Harris MF et al [42], found a small weight reduction (1.06 kg) that was achieved only among those attending the intervention group, participating in the education program. Improved glycemic control reduced microvascular and macrovascular complications associated with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in a cluster randomized controlled trial, Harris MF et al [42], found a small weight reduction (1.06 kg) that was achieved only among those attending the intervention group, participating in the education program. Improved glycemic control reduced microvascular and macrovascular complications associated with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 98%
“…[40][41][42] These studies found that they could improve referral rates through good linkages with referral services, a referral system, and structured interventions free of participation fees. The HUC implementation strategy met those conditions, with the exception of the referral system.…”
Section: Findings Compared To Those In the Literaturementioning
confidence: 99%
“…940944 Other strategies focus on changing the organization or context in which the care is delivered, including delegation of preventive services to nonphysician staff (eg, nurses or pharmacists), the use of group visits, or the implementation of clinics devoted to screening and preventive services. 943,945948 Quality improvement efforts that include activities that focus on the system, the provider, and the patient, as well as the coordination of services across these domains, are often the most effective. 949 Studies examining the effectiveness of stroke education programs have generally identified a modest effect on patient knowledge, risk perception, or health beliefs.…”
Section: Strategies To Improve Preventive Vascular Health Servicesmentioning
confidence: 99%